THE RELATIONSHIP BETWEEN CHILD ABUSE AND FAMILY, PSYCHOLOGICAL AND SOCIAL FACTORS AMONG CHILDREN - Gorjian, Z.; Mahmoodi, N.; Nabhani, N.; Mohseni, A.; Baghbani, M.; Zahedi, A.; Azadpour, Sh. (University of Eloued جامعة الوادي, 2017)
Introduction: Child abuse is a social problem that affects childrenâ€™s life in the society. Although there is not a sophisticated statistic on this problem and its epidemic issue in Iran, itsshort and long-term effects have been shown in several studies. Thus, this research aimed at investing the epidemic effect of child abuse and its relationship with other factors including family, logical and social factors. Materials and Methodology: This study was a cross-sectional descriptive research that examines 592 children at the sixth grade of primary comes (i.e., 12 year-primary school students) who were selected based on clusteringÂ Â sampling at the girl and boyâ€™s primary schools. The research tools for data collection were the questionnaire of multi-section including the profiles of the children and their parents and the questionnaire of child abuse. Data were coded and analyzed thought SPSS, version 19. Results: Findings showed that 41 percent of the students were abused. 99.3 percent of them were neglected or ignored. 83.6 percent of children were abused through affective (psychological) factors and 47.2 percent of children have experienced at least a case of physical (bold) abuse. 51.2 percent of the abused children were girls and the rest were boys. The highest rate of child abuse belonged to the parents (i.e., 23.9% from fathers and 18.2% from mothers). Child abused showed a direct correlation with gender (p=0.02), divorce (p=0.05), fatherâ€™s age (p=0.03), motherâ€™s age (p=0.03), number of children (p=0.04), and the child rank of birth (p=0.05). Moreover, there was negative correlation between the fathersâ€™ income (p=0.05) and the motherâ€™s educational level (p=0.005). Conclusion: Results of the study showed that child abuse is seen in families, especially the parents frequently neglect and ignore the children. Thus, there is a need to protect the children through establishing strict rules and preventing programs. This requires training programs in the mass media to prevent the spread of child abuse in the society.
Articale in Journal of fundamental and Applied Sciences Vol. 09, N. 03
Keywords: Affective factors, Child abuse, Physical factors, Negligence